Zoomorphic and Phytomorphic Images in A. S. Pushkin’s Fairy Tales and Their Translations into Chinese Language - J. Wu (Научный диалог, 2017)
The results of a comparative analysis of zoomorphic and phytomorphic images reflected in the metaphors and comparisons in A. S. Pushkin’s fairy tales and their modern translations into Chinese language, made by Tsun Yuy and Ma Sinshuy are presented. The relevance of the study of creativity of A. S. Pushkin in the aspect of translation of his works into Chinese is determined by the interest of the Chinese reader to the works of Russian classics; the significance of the fairy tale as a genre, reflecting the people’s view of the world; the attention of modern linguistics to the issues of worldview and the characteristics of idiostyle of the author. The novelty of the work is determined by appeal to the new, not yet subjected to the philological study translations of Pushkin’s fairy tales. Specifics of translation of comparative tropes in fairy tales of the poet are revealed in the light of “the cultural meanings” inherent in the images of animals and plants in views of the Russian and Chinese peoples. Zoomorphisms and phythomorphisms in accordance with the degree of equivalence of the relevant images in the views of Russian and Chinese people fall into three categories: fully equivalent, partially equivalent and non-equivalent. It is noted that the material is grouped mainly in the areas of fully and partially equivalent ratios that is explained by the known similarity of a number of images of animals and plants in two cultures. The cases of unequal ratios of the images are commented. The predominance of zoomorphic images on phytomorphic ones are emphasized and explained. The features of the transmission by the translators of the content of zoomorphic and phytomorphic Pushkin’s images for their adequate perception of Chinese readers are discussed.